Intervention planning for the REDUCE maintenance intervention: a digital intervention to reduce reulceration risk among patients with a history of diabetic foot ulcers. Issue 5 (18th May 2018) - Greenwell, Kate; Sivyer, Katy; Vedhara, Kavita; Yardley, Lucy; Game, Frances; Chalder, Trudie; Richards, Gayle; Drake, Nikki; Gray, Katie; Weinman, John; Bradbury, Katherine
Abstract : Objectives: To develop a comprehensive intervention plan for the REDUCE maintenance intervention to support people who have had diabetic foot ulcers (DFUs) to sustain behaviours that reduce reulceration risk. Methods: Theory-based, evidence-based and person-based approaches to intervention development were used. In phase I of intervention planning, evidence was collated from a scoping review of the literature and qualitative interviews with patients who have had DFUs (n=20). This was used to identify the psychosocial needs and challenges of this population and barriers and facilitators to the intervention's target behaviours: regular foot checking, rapid self-referral in the event of changes in foot health, graded and regular physical activity and emotional management. In phase II, this evidence was combined with expert consultation to develop the intervention plan. Brief 'guiding principles' for shaping intervention development were created. 'Behavioural analysis' and 'logic modelling' were used to map intervention content onto behaviour change theory to comprehensively describe the intervention and its hypothesised mechanisms. Results: Key challenges to the intervention's target behaviours included patients' uncertainty regarding when to self-refer, physical limitations affecting foot checking and physical activity and, for some, difficulties managing negative emotions. Important considerations for the intervention design included a need to increase patients' confidence in making a self-referral and in using the maintenance intervention and a need to acknowledge that some intervention content might be relevant to only some patients (emotional management, physical activity). The behavioural analysis identified the following processes hypothesised to facilitate long-term behaviour maintenance including increasing patients' skills, self-efficacy, knowledge, positive outcome expectancies, sense of personal control, social support and physical opportunity. Conclusions: This research provides a transparent description of the intervention planning for the REDUCE maintenance intervention. It provides insights into potential barriers and facilitators to the target behaviours and potentially useful behaviour change techniques to use in clinical practice.